Characteristics of Low Back Pain in Adolescent Patients With Early-Stage Spondylolysis Evaluated Using a Detailed Visual Analogue Scale. Issue 1 (1st January 2015) - Sugiura, Shiro; Aoki, Yasuchika; Toyooka, Takeshi; Shiga, Tetsuo; Otsuki, Kazumi; Aikawa, Emi; Oyama, Takato; Kitoh, Kazuhisa; Chikako, Sakaida; Takata, Yuka; Ishizaki, Tohru; Omori, Yasutaka; et al.
Abstract : Study Design: Retrospective comparative cohort study. Objective: To elucidate the characteristics of low back pain (LBP) in adolescent patients with early-stage spondylolysis (ESS). Summary of Background Data: ESS is a common cause of acute LBP in adolescents. When treating patients with ESS, early diagnosis is important; however, early diagnosis is difficult without magnetic resonance imaging. Methods: Adolescent patients (n = 77) with acute LBP showing no pathological findings on plain radiography were included (<1 m after onset). Patients were divided into ESS and nonspecific LBP (NS-LBP) groups by conducting magnetic resonance imaging; patients showing no pathological findings that explain the cause of LBP were classified as NS-LBP. LBP was evaluated using a traditional visual analogue scale (VAS; 0–10 cm), Oswestry Disability Index, and a detailed VAS scoring system in which pain is independently evaluated in 3 different postural situations (in motion, standing, and sitting); the values were compared between the 2 groups. Results: Of 77 patients, 41 (mean age: 14.6 yr; 33 adolescent boys/8 adolescent girls) had ESS and 36 (mean age: 14.3 yr; 20 adolescent boys/16 adolescent girls) were considered to have NS-LBP. Respective traditional VAS and Oswestry Disability Index scores were 4.9, 16.1 in the ESS group, and 6.2, 26.3 in the NS-LBP group. Both scores were significantly higher in the NS-LBP group. The results of the detailed VAS revealed that the ESS group showed significantly greater pain intensity while in motion than while standing or sitting (4.2, 2.0, and 2.0, respectively), whereas the NS-LBP group showed similar pain intensities in all 3 postural situations (5.3, 4.0, and 4.9, respectively). Conclusion: This study revealed that LBP characteristics may provide important information for distinguishing ESS from other low back disorders. Because early diagnosis is essential for the treatment of ESS, MRI examination is recommended for patients showing severe pain in motion, but less pain when standing or sitting. Level of Evidence: 3 Abstract : The characteristics of low back pain in adolescent patients with early-stage spondylolysis (ESS) were elucidated using a detailed visual analogue scale (VAS). The results of the detailed VAS revealed that the ESS group showed significantly greater pain intensity while in motion, than when standing or sitting.